2011
DOI: 10.1086/522269
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Methicillin-Resistant Staphylococcus aureus Prevalence among S. aureus Isolates on Surgical Site Infection Risk after Coronary Artery Bypass Surgery

Abstract: OBJECTIVE-Cephalosporins are recommended for antibiotic prophylaxis to prevent cardiothoracic surgical site infections (SSIs) except in patients with β-lactam allergy or in settings with a "high" prevalence of methicillin-resistant Staphylococcus aureus (MRSA) among S. aureus isolates (hereafter, "MRSA prevalence"); however, "high" remains undefined. We sought to identify the MRSA prevalence at which glycopeptide prophylaxis would minimize SSIs relative to β-lactam prophylaxis.METHODS-We developed a decision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For CABG surgery, the authors of two studies have recommended a MRSA prevalence threshold of 3% among infections caused by S. aureus (24)(25)(26). Miller et al (27) suggested that lower rates of MRSA prevalence (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For CABG surgery, the authors of two studies have recommended a MRSA prevalence threshold of 3% among infections caused by S. aureus (24)(25)(26). Miller et al (27) suggested that lower rates of MRSA prevalence (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…63 Current clinical practice guidelines for antimicrobial prophylaxis in surgery, as supported by the American Society of Health-System Pharmacists, the Infectious Diseases Society of America, the Surgical Infection Society, and the Society for Healthcare Epidemiology of America, do recommend a single perioperative dose of intravenous vancomycin instead in those patients known to be methicillin-resistant S. aureus-colonized regardless of preoperative decolonization protocol; glycopeptide (e.g., vancomycin) prophylaxis has only been demonstrated to be cost-effective when used routinely where methicillin-resistant S. aureus prevalence rates exceed 10 percent. 64 In addition, if methicillin-resistant S. aureus postoperative infections become a significant portion of the practicing surgeon's complication rate (as identified by epidemiologically linked clusters of methicillin-resistant S. aureus infections), we recommend active surveillance of the surgeons and health care workers and the patient. A similar protocol for methicillin-resistant S. aureus outbreaks has proven effective in other case series involving soft-tissue infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have developed decision analysis models to determine the threshold of MRSA prevalence at which vancomycin would minimize the incidence and cost of SSI. For CABG surgery, the authors of two studies have recommended a MRSA prevalence threshold of 3% among infections caused by S. aureus …”
Section: Question 7: Is There Evidence To Support the Routine Use Of mentioning
confidence: 99%